Immobilized Carbohydrates for Preparation of 3'-Glycoconjugated Oligonucleotides - Österlund Tommi; Aho Aapo; Äärelä Antti; Tähtinen Ville; Korhonen Heidi; Virta Pasi (John Wiley & Sons, Inc., 2025)
A detailed protocol for preparation 3'-glycoconjugated oligonucleotides is described based on one-pot immobilization of 4,4'-dimethoxytrityl-protected carbohydrates to a solid support followed by on-support peracetylation and automated oligonucleotide assembly. Compared to an appropriate building block approach and post-synthetic manipulation of oligonucleotides, this protocol may simplify the synthesis scheme and increase overall yield of the conjugates. Furthermore, the immobilization to a solid support typically increases the stability of reactants, enabling prolonged storage, and makes subsequent processing convenient. Automated assembly on these carbohydrate-modified supports using conventional phosphoramidite chemistry produces 3'-glycoconjugated oligonucleotides in relatively high yield and purity. © 2020 Wiley Periodicals LLC. Basic Protocol 1: Synthesis of 1-O-tert-butyldimethylsilyl-6-O-(4,4'-dimethoxytrityl)-β-D-glucose Basic Protocol 2: Synthesis of 6-O-dimethoxytrityl-2,3,1',3',4',6'-hexa-O-benzoylsucrose Basic Protocol 3: Synthesis of 6″-O-dimethoxytrityl-N-trifluoroacetyl-protected aminoglycosides Basic Protocol 4: Synthesis of 3-O-dimethoxytrityl-propyl β-D-galactopyranoside Basic Protocol 5: Synthesis of trivalent N-acetyl galactosamine cluster Basic Protocol 6: Synthesis of carbohydrate monosuccinates and their immobilization to a solid support Basic Protocol 7: Oligonucleotide synthesis using immobilized carbohydrates.